1997
DOI: 10.1161/01.cir.96.7.2397
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Renin-Angiotensin Pathway Through Enzyme Inhibition and Specific Receptor Blockade in Pacing-Induced Heart Failure

Abstract: The unique findings of this study were twofold. First, basic defects in specific components of the myocyte excitation-contraction coupling process that occur with CHF are reversible. Second, combined ACEI and AT1 Ang II blockade may provide unique benefits on myocyte contractile processes in the setting of CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 48 publications
4
42
0
Order By: Relevance
“…28 Previous reports have suggested that valsartan, a highly selective antagonist of the AT 1 receptor, is useful in lowering cardiovascular risk. 18,29,30 This drug, beyond its blood pressure-lowering activity, improves heart failure in rats with myocardial infarction, reduces endothelial dysfunction and intimal thickening in atherosclerotic rabbits, and induces a significant regression of left ventricular hypertrophy in patients with essential hypertension. 18,[31][32][33] The effects of AT 1 antagonists on fibrinolytic balance, and in particular on PAI-1 and tPA plasma levels, in normal subjects as well as in patients with cardiovascular disease, are still controversial.…”
mentioning
confidence: 99%
“…28 Previous reports have suggested that valsartan, a highly selective antagonist of the AT 1 receptor, is useful in lowering cardiovascular risk. 18,29,30 This drug, beyond its blood pressure-lowering activity, improves heart failure in rats with myocardial infarction, reduces endothelial dysfunction and intimal thickening in atherosclerotic rabbits, and induces a significant regression of left ventricular hypertrophy in patients with essential hypertension. 18,[31][32][33] The effects of AT 1 antagonists on fibrinolytic balance, and in particular on PAI-1 and tPA plasma levels, in normal subjects as well as in patients with cardiovascular disease, are still controversial.…”
mentioning
confidence: 99%
“…2 However, the clinical syndrome of heart failure is the final state of a wide spectrum of diseases affecting the heart 1,26 and the effects of RAS inhibition may differ according to the causation, genetic and environmental backgrounds, and disease stage. To gain insights into the in vivo effects of RAS inhibition on the development and progression of heart failure, several animal models have been utilized; [8][9][10][11][12][13][14][15][16]27 however, most do not perfectly represent human heart failure, 28 and the effects of RAS inhibition are unknown in a mouse model of DCM caused by mutations affecting the cytoskeleton and sarcomere. In this regard, we are the first to analyze the preventive effects of AT1a receptor blockade on progression of heart failure in MLP-deficient cardiomyopathic mice.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 These cellular alterations that occur within the heart would promote left ventricular (LV) remodeling and contribute to the progression of heart failure. However, the effects of the AT1 receptor have been experimentally verified only in animal models of heart failure, such as a myocardial infarction model produced by coronary artery ligation, 7-9 a pacing-induced heart failure model, 10 Dahl salt-sensitive rats, 11 a pressure-overloaded model, 12,13 a shunt-induced volume-overloaded model, 14 experimental myocarditis, 15 and doxorubicininduced cardiomyopathy. 16 A number of reports have suggested that inhibition of the AT1 receptor prevents LV remodeling after myocardial infarction, 2,7-9 but it remains unknown whether it is also beneficial for dilated cardiomyopathy (DCM).…”
mentioning
confidence: 99%
“…As previously described, myocardial ACE activity was determined with the synthetic substrate Hip-His-Leu by a modified procedure. 12 All assays were performed in duplicate.…”
Section: Measurement Of the Components Of Rasmentioning
confidence: 99%